Pengaruh Pengembangan Karir dan Komitmen Karyawan Terhadap Kinerja Karyawan pada Rumah Sakit Ibunda Bagan Batu, Provinsi Riau - Wahyu Pradika; Riza Indriani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to explore the influence of career development, employee commitment, and joint career development with commitment on employee performance at Ibunda Bagan Batu Hospital, Riau. The research method employs a quantitative approach with total sampling technique involving 75 employees of Ibunda Bagan Batu Hospital. Data were collected through literature study, interviews, observations, and questionnaires, and analyzed using instrument validity tests, classical assumptions, multiple linear regression, and hypothesis testing. Data management was conducted using SPSS 26 for Windows. The results indicate that career development (X1) (coefficient: 0.284) and employee commitment (X2) (coefficient: 0.272) positively and significantly influence employee performance (Y) at Ibunda Bagan Batu Hospital. The implications of this research underscore the importance of training programs and integration between career development and employee commitment to enhance employee performance.